COLLABORATIVE LEARNING DALAM PENINGKATAN KAPASITAS GURU MENYUSUN PERANGKAT PEMBELAJARAN NUMERASI DI SMP KOTA PALEMBANG - Ratu Ilma Indra Putri; Zulkardi; Elika Kurniadi; Weni Dwi Pratiwi; Rini Herlina; Laela Sagita; Hasbi Ramadhan; Allen Marga Retta; Anggria Septiani Mulbasari; Viona Adelia; Nabila Putri Isamer; Atikarani Noer Saleha (Jurnal Berdaya Mandiri, 2022)
Teacher innovation in designing interesting learning requires continuous improvement of abilities. The learning assessment paradigm that revolves around the Asasemen Kopetnsi Minimum (AKM) where one of them is numeracy or also called numeracy literacy and mathematical literacy. A problem was found in teachers at the Palembang City MGMP in Difficulty in compiling learning tools that strengthen students' numeracy skills. Through training and mentoring in the learning community or collaborative learning, selecting KD for numeracy strengthening, determining numeracy demands for the KD, determining numeracy activities that can be embedded in learning, and determining mathematical tools and mathematical terms (terminology) used in activities. The results show that the teacher is able to use contexts that are close to the daily lives of students in learning. keyword: Collaborative Learning, Learning Tools, Numeracy